HILITE-A well-defined ion target for laser experiments - Stallkamp, N.; Ringleb, S.; Arndt, B.; Kiffer, M.; Kumar, S.; Paulus, Gerhard G.; Quint, W.; Stoehlker, Th; Vogel, M. (Journal of Physics: Conference Series, 2020)
We present a Penning-trap-based setup for the study of light-matter interactions in the high-power and/or high-intensity laser regime, such as multi-photon ionization and field ionization. The setup applies ioncloud formation techniques to highly charged ions to the end of specific target preparation, as well as nondestructive detection techniques to identify and quantify the interaction educts and products.
CRIS-Team Scopus Importer:2023-04-20